Construction Of Moral-Based Islamic Learning For Integrated Islamic High School Students In Sumbawa Regency - Muammar Khadafie; M. Sobry (Journal of Multidisciplinary Science, 2022)
Learning is a vital part of human life. Learning (especially Islam), with its various styles, is oriented towards providing provisions to humans (students) to achieve happiness in the world and the hereafter. One of the processes that deliver this is integrated Islamic learning based on the morals of SMAIT students. It will provide provisions for moral learning in the four scopes of the environment: family, school, community, and social media. This research is qualitative research with a qualitative descriptive approach. It uses Piaget's constructivism theory with the assimilation and accommodation method as the grand theory and the Al-Ghazali method as the supporting theory. Data collection was carried out using observation, interviews, and documentation techniques. In this research, researchers involved figures in learning institutions such as leaders of boarding schools or institutions, teachers, guardians of students (student guardians), and students. The results of this study indicate that the application of different methods in the implementation strategy has an impact on increasing greetings, discipline, ethics in social interaction, and social media among fellow students, parents, teachers, and the community who are part of the social context. This impact is well implemented at the four environmental levels of the study.